Ternary Bulk Heterojunction Photoactive Layer for Organic Solar Cells - Sbei, M. A.; Derouiche, H. (New Ideas Concerning Science and Technology Vol. 4, 2021)
A ternary thin film has been fabricated using poly(3-hexylthiophene) (P3HT) / copper phthalocyanine (CuPc)/ [6,6]-phényl-C61-butanoate de méthyle (PCBM) and deposed between an indium tin oxide (ITO)/ poly(3,4-ethylenedioxythiophene): Poly(styrene sulfonate) (PEDOT/PSS) photoanode and a D-?-A indoline (D129)/ aluminium photocathode. The thin films have been characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM) and ultraviolet/visible spectroscopy in order to study the influence of adding P3HT on the morphological, structural and optical properties of the photoactive layer. We have also compared the I-V characteristics of ITO/ PEDOT:PSS/ CuPc0.5: PCBM0.5/ D129/ Al and ITO/ PEDOT:PSS/ P3HT0.3:CuPc0.3:PCBM0.4/ D129/ Al organic solar cells with and with and without annealing. Both structures show good open-circuit voltage and Fill Factor. Indeed, the incorporation of P3HT into CuPc:PCBM thin film improves all the photovoltaic properties.